Exploration of personal ethics: an in-class case exercise for business ethics students to help them develop personal values - Sundararajan, Malavika (Journal of Management and Business Education, 2021)
The paper presents an in-class case exercise that aims to help students learn how to apply ethical values in their personal and professional lives. Development of ethical values are often stated in a very simple way and seem easy to apply to objective situations in an ethical course. However, when it comes to having students apply it in their lives, there seems to be a disconnect, due to a level of unawareness of one’s own actions. The exercise is thus designed to help students gain self-awareness of personal practices in different contexts. The exercise will help students develop individual ethical values in each of those contexts especially if their personal practices seem inadequate in helping them achieve their desires. While the immediate audience includes undergraduate and graduate students, it would be a valuable self-exploratory tool to use in any workplace setting to train employees.